A preparation method of potassium sodium niobate-based lead-free piezoelectric ceramic
Highly active KNN ceramics were synthesized by the two-step molten salt method and specific components were introduced to form a three-phase-tetragonal phase boundary, which solved the problem of poor piezoelectric properties of potassium niobate-based lead-free piezoelectric ceramics, and achieved excellent piezoelectric properties and denser and uniform microstructure.
Patent Information
- Application Number
- CN202411825607.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-12
AI Technical Summary
As a lead-free piezoelectric ceramic material, potassium sodium niobate has poor piezoelectric properties and is difficult to meet the application needs of small components and precision instrument control equipment.
A two-step molten salt method was used to synthesize highly active and high-purity KNN ceramic powders, and Bi0.5Na0.5Ti1-x(W2/3Y1/3)xO3 and (Li1-yAgy)SbO3 were introduced as new components to form a three-phase-tetragonal phase boundary to improve piezoelectric performance.
It significantly improves the piezoelectric properties of potassium niobate-based lead-free piezoelectric ceramics, so that they can meet the application needs of small components and precision instrument control equipment, while avoiding the influence of impurities and reducing the generation of impurities.
Smart Images

Figure CN119285355B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of piezoelectric ceramic materials, in particular to a method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics. Background Art
[0002] Piezoelectric ceramic materials are the most widely used and most frequently used piezoelectric materials. They are a very important type of high-tech new functional materials. In today's information industry era, piezoelectric ceramic materials are widely used in many high-tech fields such as electronics and optoelectronics. Lead zirconate titanate (PZT) piezoelectric ceramics have always occupied a dominant position. However, since the lead content in PZT-based ceramics exceeds 60%, the preparation, use and treatment of materials have caused great harm to the environment. Therefore, whether it is to save energy or to protect the environment, it is imperative for humans to develop non-lead-based piezoelectric ceramic materials for their own sustainable development. Potassium sodium niobate has been widely studied as an important lead-free piezoelectric ceramic, but due to its poor piezoelectric properties, it is difficult to meet the application needs of small components, precision instrument control and other equipment. Summary of the invention
[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics.
[0004] The technical solutions adopted are as follows:
[0005] A method for preparing potassium sodium niobate-based lead-free piezoelectric ceramics is as follows:
[0006] First, K2CO3 and Nb2O5 are used as raw materials, KCl is used as molten salt, mixed and ball-milled, and then dried, and then kept at 800-850°C for 1-5 hours to synthesize a precursor, the precursor is repeatedly washed with hot deionized water and then dried, and then mixed with K2CO3 and Na2CO3, KCl and NaCl are used as molten salts, mixed and ball-milled, and then dried, and then kept at 900-950°C for 1-5 hours, and the resulting product is repeatedly washed with hot deionized water and dried to obtain KNN prefabricated powder;
[0007] Bi2O3, Na2CO3, TiO2, WO3 and Y2O3 are mixed and ball-milled, dried, and then pre-calcined at 800-900°C for 1-5h to obtain BNT prefabricated powder;
[0008] Li2CO3, Ag2O and Sb2O3 are mixed and ball-milled, dried, and then pre-calcined at 800-900°C for 1-5h to obtain LS preformed powder;
[0009] The KNN preformed powder, BNT preformed powder and LS preformed powder are mixed again, ball-milled and dried, and a binder is added to granulate, sieve and press to obtain a green body. The green body is first heated to 500-600°C for heat preservation and debinding for 1-5 hours, and then heated to 1000-1150°C for heat preservation and sintering for 1-5 hours.
[0010] Furthermore, the chemical structure formula of the potassium sodium niobate-based lead-free piezoelectric ceramic is as follows:
[0011] (K 0.5 Na 0.5 )NbO3-αwt%Bi 0.5 Na 0.5 Ti 1-x (W 2 / 3 Y 1 / 3 ) x O3-βwt%(Li 1-y Ag y )SbO3
[0012] Among them, 0<x≤0.05, 0.1≤y≤0.3;
[0013] 1≤α≤5, 1≤β≤5.
[0014] Further, 0.02≤x≤0.04, 0.15≤y≤0.25.
[0015] x can be 0.02, 0.021, 0.022, 0.023, 0.024, 0.025, 0.026, 0.027, 0.028, 0.029, 0.03, 0.031, 0.032, 0.033, 0.034, 0.035, 0.036, 0.037, 0.038, 0.039, 0.04, which are only listed for ease of understanding and are not intended to be limiting;
[0016] y can be 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, which are only listed for ease of understanding and are not intended to be limiting;
[0017] Further, x=0.03, y=0.2.
[0018] Furthermore, 2≤α≤3, 3≤β≤4.
[0019] α can be 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, which are only listed for ease of understanding and are not intended to be limiting;
[0020] β can be 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4, which are only listed for ease of understanding and are not intended to be limiting;
[0021] Further, α=2.5, β=3.5.
[0022] Furthermore, the binder is a polyvinyl alcohol aqueous solution with a mass concentration of 3-8wt%.
[0023] Furthermore, the pressure during pressing is 100-200 MPa.
[0024] Furthermore, the heating rate in the first stage of heating is 1-5°C / min, and the heating rate in the second stage of heating is 10-30°C / min.
[0025] Beneficial effects of the present invention:
[0026] The present invention provides a method for preparing a lead-free potassium sodium niobate-based piezoelectric ceramic, which can synthesize a high-activity, high-purity KNN ceramic powder by a two-step molten salt method, thereby improving the piezoelectric properties of the NKN ceramic, and also avoiding the influence of impurity ions and not easily generating impure phases;
[0027] The introduction of Bi can induce the formation of rhombohedral phase 0.5 Na 0.5 Ti 1-x (W 2 / 3 Y 1 / 3 ) x O3 and (Li 1-y Ag y )SbO3, as a new component, can form a rhombohedral-tetragonal phase boundary in potassium sodium niobate-based lead-free piezoelectric ceramics, so that potassium sodium niobate-based lead-free piezoelectric ceramics exhibit the strongest piezoelectric properties near the phase boundary. In addition, both of them have a perovskite structure, which can not only form a single and stable perovskite structure with KNN solid solution, but also effectively improve the movement of electric domains by adjusting the doping ions and controlling the degree of lattice distortion of piezoelectric ceramics, thereby further improving the piezoelectric properties of piezoelectric ceramics and helping to obtain a denser and more uniform microstructure;
[0028] The potassium sodium niobate-based lead-free piezoelectric ceramic prepared by the present invention has high density and excellent piezoelectric properties, and can meet the application requirements of small components, precision instrument control and other equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the potassium sodium niobate-based lead-free piezoelectric ceramic prepared in Example 1. DETAILED DESCRIPTION
[0030] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0031] Embodiment 1:
[0032] This embodiment provides a method for preparing a lead-free potassium sodium niobate-based piezoelectric ceramic:
[0033] The chemical structure formula of the prepared potassium sodium niobate-based lead-free piezoelectric ceramics is as follows:
[0034] (K 0.5 Na 0.5 )NbO3-2.5wt%Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 O3-3.5wt%(Li 0.8 Ag 0.2 )SbO3
[0035] First, K2CO3 and Nb2O5 with a molar ratio of 1:1 were used as raw materials, and KCl with the same total mass as the raw materials was used as molten salt. The raw materials and molten salt were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 hours in a planetary ball mill, the mixture was dried in an oven, and then kept at 850°C for 2 hours to synthesize a precursor. The precursor was repeatedly washed with hot deionized water until no Cl was identified using an AgNO3 solution. - Until, the washed precursor is dried, according to (K 0.5 Na 0.5 )NbO3 stoichiometric ratio Precursor, K2CO3 and Na2CO3 were weighed as raw materials, KCl and NaCl with a molar ratio of 1:1 were used as molten salt, and the mass of molten salt was 50% of the mass of raw materials. The raw materials and molten salt were added to the ball mill again, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling in a planetary ball mill for 20 hours, they were dried in an oven and then kept at 950℃ for 4 hours. The obtained product was repeatedly washed with hot deionized water until no Cl was identified using AgNO3 solution. - The washed product is dried to obtain KNN preformed powder;
[0036] According to Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03Bi2O3, Na2CO3, TiO2, WO3 and Y2O3 were weighed in a stoichiometric ratio in O3, added into a ball mill, and milled in a planetary ball mill for 20 h using anhydrous ethanol as a ball milling medium, dried in an oven, and then pre-calcined at 850 °C for 2 h to obtain BNT prefabricated powder;
[0037] According to (Li 0.8 Ag 0.2 ) Li2CO3, Ag2O and Sb2O3 were weighed in a ball milling jar, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 h in a planetary ball mill, the mixture was dried in an oven, and then pre-calcined at 900°C for 2 h to obtain LS preformed powder;
[0038] KNN preformed powder, BNT preformed powder and LS preformed powder are added to a ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball-milled in a planetary ball mill for 10 hours and then dried in an oven, polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added to a mold, and pressed at 100MPa to obtain a green body, the green body is first heated to 600℃ at a speed of 1℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1000℃ at a speed of 10℃ / min in a second stage, kept warm and sintered for 4 hours.
[0039] Embodiment 2:
[0040] This embodiment provides a method for preparing a lead-free potassium sodium niobate-based piezoelectric ceramic:
[0041] The chemical structure formula of the prepared potassium sodium niobate-based lead-free piezoelectric ceramics is as follows:
[0042] (K 0.5 Na 0.5 )NbO3-2.5wt%Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 O3-3.5wt%(Li 0.8 Ag 0.2 )SbO3
[0043] First, K2CO3 and Nb2O5 with a molar ratio of 1:1 were used as raw materials, and KCl with the same total mass as the raw materials was used as molten salt. The raw materials and molten salt were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 hours in a planetary ball mill, the mixture was dried in an oven, and then kept at 850°C for 2 hours to synthesize a precursor. The precursor was repeatedly washed with hot deionized water until no Cl was identified using an AgNO3 solution. - Until, the washed precursor is dried, according to (K0.5 Na 0.5 )NbO3 stoichiometric ratio Precursor, K2CO3 and Na2CO3 were weighed as raw materials, KCl and NaCl with a molar ratio of 1:1 were used as molten salt, and the mass of molten salt was 50% of the mass of raw materials. The raw materials and molten salt were added to the ball mill again, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling in a planetary ball mill for 20 hours, they were dried in an oven and then kept at 950℃ for 4 hours. The obtained product was repeatedly washed with hot deionized water until no Cl was identified using AgNO3 solution. - The washed product is dried to obtain KNN preformed powder;
[0044] According to Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 Bi2O3, Na2CO3, TiO2, WO3 and Y2O3 were weighed in a stoichiometric ratio in O3, added into a ball mill, and milled in a planetary ball mill for 20 h using anhydrous ethanol as a ball milling medium, dried in an oven, and then pre-calcined at 850 °C for 2 h to obtain BNT prefabricated powder;
[0045] According to (Li 0.8 Ag 0.2 ) Li2CO3, Ag2O and Sb2O3 were weighed in a ball milling jar, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 h in a planetary ball mill, the mixture was dried in an oven, and then pre-calcined at 900°C for 2 h to obtain LS preformed powder;
[0046] KNN preformed powder, BNT preformed powder and LS preformed powder are added to a ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball-milled in a planetary ball mill for 10 hours and then dried in an oven, polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added to a mold, and pressed at 100MPa to obtain a green body, the green body is first heated to 600℃ at a speed of 1℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1050℃ at a speed of 10℃ / min in a second stage, kept warm and sintered for 4 hours.
[0047] Embodiment 3:
[0048] This embodiment provides a method for preparing a lead-free potassium sodium niobate-based piezoelectric ceramic:
[0049] The chemical structure formula of the prepared potassium sodium niobate-based lead-free piezoelectric ceramics is as follows:
[0050] (K 0.5 Na 0.5)NbO3-2.5wt%Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 O3-3.5wt%(Li 0.8 Ag 0.2 )SbO3
[0051] First, K2CO3 and Nb2O5 with a molar ratio of 1:1 were used as raw materials, and KCl with the same total mass as the raw materials was used as molten salt. The raw materials and molten salt were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 hours in a planetary ball mill, the mixture was dried in an oven, and then kept at 850°C for 2 hours to synthesize a precursor. The precursor was repeatedly washed with hot deionized water until no Cl was identified using an AgNO3 solution. - Until, the washed precursor is dried, according to (K 0.5 Na 0.5 )NbO3 stoichiometric ratio Precursor, K2CO3 and Na2CO3 were weighed as raw materials, KCl and NaCl with a molar ratio of 1:1 were used as molten salt, and the mass of molten salt was 50% of the mass of raw materials. The raw materials and molten salt were added to the ball mill again, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling in a planetary ball mill for 20 hours, they were dried in an oven and then kept at 950℃ for 4 hours. The obtained product was repeatedly washed with hot deionized water until no Cl was identified using AgNO3 solution. - The washed product is dried to obtain KNN preformed powder;
[0052] According to Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 Bi2O3, Na2CO3, TiO2, WO3 and Y2O3 were weighed in a stoichiometric ratio in O3, added into a ball mill, and milled in a planetary ball mill for 20 h using anhydrous ethanol as a ball milling medium, dried in an oven, and then pre-calcined at 850 °C for 2 h to obtain BNT prefabricated powder;
[0053] According to (Li 0.8 Ag 0.2 ) Li2CO3, Ag2O and Sb2O3 were weighed in a ball milling jar, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 h in a planetary ball mill, the mixture was dried in an oven, and then pre-calcined at 900°C for 2 h to obtain LS preformed powder;
[0054] KNN preformed powder, BNT preformed powder and LS preformed powder are added to a ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball-milled in a planetary ball mill for 10 hours and then dried in an oven, polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added to a mold, and pressed at 100MPa to obtain a green body, the green body is first heated to 600℃ at a speed of 1℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1100℃ at a speed of 10℃ / min in a second stage, kept warm and sintered for 4 hours.
[0055] Embodiment 4:
[0056] This embodiment provides a method for preparing a lead-free potassium sodium niobate-based piezoelectric ceramic:
[0057] The chemical structure formula of the prepared potassium sodium niobate-based lead-free piezoelectric ceramics is as follows:
[0058] (K 0.5 Na 0.5 )NbO3-2.5wt%Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 O3-3.5wt%(Li 0.8 Ag 0.2 )SbO3
[0059] First, K2CO3 and Nb2O5 with a molar ratio of 1:1 were used as raw materials, and KCl with the same total mass as the raw materials was used as molten salt. The raw materials and molten salt were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 hours in a planetary ball mill, the mixture was dried in an oven, and then kept at 850°C for 2 hours to synthesize a precursor. The precursor was repeatedly washed with hot deionized water until no Cl was identified using an AgNO3 solution. - Until, the washed precursor is dried, according to (K 0.5 Na 0.5 )NbO3 stoichiometric ratio Precursor, K2CO3 and Na2CO3 were weighed as raw materials, KCl and NaCl with a molar ratio of 1:1 were used as molten salt, and the mass of molten salt was 50% of the mass of raw materials. The raw materials and molten salt were added to the ball mill again, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling in a planetary ball mill for 20 hours, they were dried in an oven and then kept at 950℃ for 4 hours. The obtained product was repeatedly washed with hot deionized water until no Cl was identified using AgNO3 solution. - The washed product is dried to obtain KNN preformed powder;
[0060] According to Bi 0.5 Na 0.5Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 Bi2O3, Na2CO3, TiO2, WO3 and Y2O3 were weighed in a stoichiometric ratio in O3, added into a ball mill, and milled in a planetary ball mill for 20 h using anhydrous ethanol as a ball milling medium, dried in an oven, and then pre-calcined at 850 °C for 2 h to obtain BNT prefabricated powder;
[0061] According to (Li 0.8 Ag 0.2 ) Li2CO3, Ag2O and Sb2O3 were weighed in a ball milling jar, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 h in a planetary ball mill, the mixture was dried in an oven, and then pre-calcined at 900°C for 2 h to obtain LS preformed powder;
[0062] KNN preformed powder, BNT preformed powder and LS preformed powder are added to a ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball-milled in a planetary ball mill for 10 hours and then dried in an oven, polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added to a mold, and pressed at 100MPa to obtain a green body, the green body is first heated to 600℃ at a speed of 1℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1150℃ at a speed of 10℃ / min in a second stage, kept warm and sintered for 4 hours.
[0063] Comparative Example 1:
[0064] It is basically the same as Example 1, except that Bi 0.5 Na 0.5 TiO3 replaces Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 O3.
[0065] This comparative example provides a method for preparing a lead-free piezoelectric ceramic based on potassium sodium niobate:
[0066] The chemical structure formula of the prepared potassium sodium niobate-based lead-free piezoelectric ceramics is as follows:
[0067] (K 0.5 Na 0.5 )NbO3-2.5wt%Bi 0.5 Na 0.5 TiO3-3.5wt%(Li 0.8 Ag 0.2 )SbO3
[0068] First, K2CO3 and Nb2O5 with a molar ratio of 1:1 were used as raw materials, and KCl with the same total mass as the raw materials was used as molten salt. The raw materials and molten salt were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 hours in a planetary ball mill, the mixture was dried in an oven, and then kept at 850°C for 2 hours to synthesize a precursor. The precursor was repeatedly washed with hot deionized water until no Cl was identified using an AgNO3 solution. - Until, the washed precursor is dried, according to (K 0.5 Na 0.5 )NbO3 stoichiometric ratio Precursor, K2CO3 and Na2CO3 were weighed as raw materials, KCl and NaCl with a molar ratio of 1:1 were used as molten salt, and the mass of molten salt was 50% of the mass of raw materials. The raw materials and molten salt were added to the ball mill again, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling in a planetary ball mill for 20 hours, they were dried in an oven and then kept at 950℃ for 4 hours. The obtained product was repeatedly washed with hot deionized water until no Cl was identified using AgNO3 solution. - The washed product is dried to obtain KNN preformed powder;
[0069] According to Bi 0.5 Na 0.5 Bi2O3, Na2CO3 and TiO2 were weighed in a stoichiometric ratio in TiO3, added into a ball mill, and milled in a planetary ball mill for 20 h using anhydrous ethanol as a ball milling medium, dried in an oven, and then pre-calcined at 850°C for 2 h to obtain BNT preformed powder;
[0070] According to (Li 0.8 Ag 0.2 ) Li2CO3, Ag2O and Sb2O3 were weighed in a ball milling jar, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 h in a planetary ball mill, the mixture was dried in an oven, and then pre-calcined at 900°C for 2 h to obtain LS preformed powder;
[0071] KNN preformed powder, BNT preformed powder and LS preformed powder are added to a ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball-milled in a planetary ball mill for 10 hours and then dried in an oven, polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added to a mold, and pressed at 100MPa to obtain a green body, the green body is first heated to 600℃ at a speed of 1℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1000℃ at a speed of 10℃ / min in a second stage, kept warm and sintered for 4 hours.
[0072] Comparative Example 2:
[0073] The same as Example 1, except that LiSbO3 is used instead of (Li0.8 Ag 0.2 )SbO3.
[0074] This comparative example provides a method for preparing a lead-free piezoelectric ceramic based on potassium sodium niobate:
[0075] The chemical structure formula of the prepared potassium sodium niobate-based lead-free piezoelectric ceramics is as follows:
[0076] (K 0.5 Na 0.5 )NbO3-2.5wt%Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 O3-3.5wt%LiSbO3
[0077] First, K2CO3 and Nb2O5 with a molar ratio of 1:1 were used as raw materials, and KCl with the same total mass as the raw materials was used as molten salt. The raw materials and molten salt were added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling for 20 hours in a planetary ball mill, the mixture was dried in an oven, and then kept at 850°C for 2 hours to synthesize a precursor. The precursor was repeatedly washed with hot deionized water until no Cl was identified using an AgNO3 solution. - Until, the washed precursor is dried, according to (K 0.5 Na 0.5 )NbO3 stoichiometric ratio Precursor, K2CO3 and Na2CO3 were weighed as raw materials, KCl and NaCl with a molar ratio of 1:1 were used as molten salt, and the mass of molten salt was 50% of the mass of raw materials. The raw materials and molten salt were added to the ball mill again, and anhydrous ethanol was used as the ball milling medium. After mixing and ball milling in a planetary ball mill for 20 hours, they were dried in an oven and then kept at 950℃ for 4 hours. The obtained product was repeatedly washed with hot deionized water until no Cl was identified using AgNO3 solution. - The washed product is dried to obtain KNN preformed powder;
[0078] According to Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 Bi2O3, Na2CO3, TiO2, WO3 and Y2O3 were weighed in a stoichiometric ratio in O3, added into a ball mill, and milled in a planetary ball mill for 20 h using anhydrous ethanol as a ball milling medium, dried in an oven, and then pre-calcined at 850 °C for 2 h to obtain BNT prefabricated powder;
[0079] Li2CO3 and Sb2O3 were weighed according to the stoichiometric ratio in LiSbO3, added into a ball mill, and milled in a planetary ball mill for 20 h using anhydrous ethanol as the milling medium, dried in an oven, and then pre-calcined at 900°C for 2 h to obtain LS preformed powder;
[0080] KNN preformed powder, BNT preformed powder and LS preformed powder are added to a ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball-milled in a planetary ball mill for 10 hours and then dried in an oven, polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added to a mold, and pressed at 100MPa to obtain a green body, the green body is first heated to 600℃ at a speed of 1℃ / min in one stage, kept warm for 2 hours to debind, and then heated to 1000℃ at a speed of 10℃ / min in a second stage, kept warm and sintered for 4 hours.
[0081] Comparative Example 3:
[0082] The same as Example 1, except that Bi is not added. 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y 1 / 3 ) 0.03 O3.
[0083] Comparative Example 4:
[0084] The same as Example 1, except that (Li 0.8 Ag 0.2 )SbO3.
[0085] Performance Test:
[0086] The surfaces of the potassium sodium niobate-based lead-free piezoelectric ceramics prepared in Examples 1-4 and Comparative Examples 1-4 were polished, coated with silver paste on both sides, kept at 750°C for 10 min, and finally polarized at a DC voltage of 4 kV / mm for 20 min in silicone oil at 120°C and placed for 24 hours to test their performance as samples.
[0087] The density was measured by Archimedes displacement method;
[0088] The room temperature piezoelectric constant of the sample was measured using a ZJ-3AN quasi-static piezoelectric constant tester. d 33 ;
[0089] The electromechanical coupling coefficient kp, mechanical quality factor Qm and dielectric loss tanδ (25°C, 1V, 1kHz) of the samples were measured and analyzed using a precision impedance analyzer (Agilent HP4294A).
[0090] The test results are shown in Table 1 below:
[0091] ;
[0092] Piezoelectric constant d 33 It is a parameter that characterizes the performance of piezoelectric materials. It reflects the ability of a piezoelectric body to convert mechanical energy into electrical energy (positive piezoelectric effect) or to convert electrical energy into mechanical energy (inverse piezoelectric effect). The larger the piezoelectric constant, the stronger the material's ability to convert mechanical energy into electrical energy.
[0093] The electromechanical coupling coefficient kp is a parameter that indicates the degree of coupling between the mechanical energy and electrical energy of a piezoelectric body. It is also an important physical quantity that measures the strength of the piezoelectricity of a piezoelectric material. Generally speaking, the larger the better.
[0094] The mechanical quality factor Qm indicates the size of the mechanical loss of the piezoelectric ceramic material when it resonates, and is another important parameter for measuring the performance of piezoelectric materials. The reason for the mechanical loss is the internal friction of the material. When the piezoelectric element vibrates, it consumes energy to overcome friction. The Qm of general ceramics varies greatly due to different formulations and process conditions. The higher the mechanical quality factor, the more efficient the system or component is in storing energy, and the less loss in energy loss.
[0095] Dielectric loss tanδ refers to the electrical energy lost due to heat per unit time under the action of AC voltage. Dielectric loss tanδ is one of the important quality indicators of dielectrics. For example, high-power transducers require very small material dielectric loss, otherwise the transducer will be damaged due to intense heat during operation.
[0096] It can be seen from Table 1 above that the potassium sodium niobate-based lead-free piezoelectric ceramics prepared in the present invention have excellent piezoelectric properties;
[0097] From the comparison of Examples 1-4, it can be seen that different sintering temperatures will affect the density and piezoelectric properties of potassium sodium niobate-based lead-free piezoelectric ceramics. When the sintering temperature is 1050° C., the piezoelectric properties of potassium sodium niobate-based lead-free piezoelectric ceramics are optimal.
[0098] From the comparison between Example 1 and Comparative Examples 1-2, it can be seen that the composite ion (W 2 / 3 Y 1 / 3 ) 4+ and Ag + Doping plays a positive role in improving the piezoelectric properties of potassium sodium niobate-based lead-free piezoelectric ceramics;
[0099] From the comparison between Example 1 and Comparative Examples 3-4, it can be seen that Bi 0.5 Na 0.5 Ti 0.97 (W 2 / 3 Y1 / 3 ) 0.03 O3 and (Li 0.8 Ag 0.2 )The addition of SbO3 plays a positive role in improving the piezoelectric properties of potassium sodium niobate-based lead-free piezoelectric ceramics.
[0100] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a potassium sodium niobate-based lead-free piezoelectric ceramic, characterized in that: The details are as follows: First, K2CO3 and Nb2O5 are used as raw materials, KCl is used as molten salt, mixed and ball-milled, and then dried, and then kept at 800-850°C for 1-5 hours to synthesize a precursor, the precursor is repeatedly washed with hot deionized water and then dried, and then mixed with K2CO3 and Na2CO3, KCl and NaCl are used as molten salts, mixed and ball-milled, and then dried, and then kept at 900-950°C for 1-5 hours, and the resulting product is repeatedly washed with hot deionized water and dried to obtain KNN prefabricated powder; Bi2O3, Na2CO3, TiO2, WO3 and Y2O3 are mixed and ball-milled, dried, and then pre-calcined at 800-900°C for 1-5h to obtain BNT prefabricated powder; Li2CO3, Ag2O and Sb2O3 are mixed and ball-milled, dried, and then pre-calcined at 800-900°C for 1-5h to obtain LS preformed powder; The KNN preformed powder, BNT preformed powder and LS preformed powder are mixed again, ball-milled and dried, and a binder is added to granulate, sieve and press to obtain a green body, and the green body is heated to 500-600°C for heat preservation and debinding for 1-5 hours, and then heated to 1000-1150°C for heat preservation and sintering for 1-5 hours in a second stage; The general chemical structure formula of the potassium sodium niobate-based lead-free piezoelectric ceramic is as follows: <h2 style=";text-align:left;direction:ltr">(K<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Na<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> )NbO3-αwt%Bi<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Na<h2 style=";text-align:left;direction:ltr"> 0.5 <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> (W<h2 style=";text-align:left;direction:ltr"> 2 / 3 <h2 style=";text-align:left;direction:ltr"> Y<h2 style=";text-align:left;direction:ltr"> 1 / 3 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> O3-βwt%(Li<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Ag<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> SbO3 Among them, 0<x≤0.05, 0.1≤y≤0.3; 1≤α≤5,1≤β≤5。 2. The method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic according to claim 1, characterized in that: 0.02≤x≤0.04, 0.15≤y≤0.
25.
3. The method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic according to claim 1, characterized in that: x=0.03,y=0.
2.
4. The method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic according to claim 1, characterized in that: 2≤α≤3,3≤β≤4。 5. The method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic according to claim 1, characterized in that: α=2.5,β=3.5。 6. The method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic according to claim 1, characterized in that: The binder is a polyvinyl alcohol aqueous solution with a mass concentration of 3-8wt%.
7. The method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic according to claim 1, characterized in that: The pressure during pressing is 100-200MPa.
8. The method for preparing the potassium sodium niobate-based lead-free piezoelectric ceramic according to claim 1, characterized in that: The heating rate during the first stage of heating is 1-5°C / min, and the heating rate during the second stage of heating is 10-30°C / min.
Citation Information
Patent Citations
Potassium-bismuth titanate-based solid solution lead-free piezoelectric ceramic and manufacturing method thereof
CN101973763A
Low-loss sodium potassium niobate-based lead-free piezoelectric ceramics sintered at low temperature and preparation method thereof
CN102329133A